[ 18 F]-Fluorodeoxyglucose Uptake in Lymphoid Tissue Serves as a Predictor of Disease Outcome in the Nonhuman Primate Model of Monkeypox Virus Infection - Dyall, Julie; Johnson, Reed F.; Chefer, Svetlana; Leyson, Christopher; Thomasson, David; Seidel, Jurgen; Ragland, Dan R.; Byrum, Russell; Jett, Catherine; Cann, Jennifer A.; St. Claire, Marisa; Jagoda, Elaine; et al. (Journal of virology, 2017)
Real-time bioimaging of infectious disease processes may aid countermeasure development and lead to an improved understanding of pathogenesis. However, few studies have identified biomarkers for monitoring infections using in vivo imaging. Previously, we demonstrated that positron emission tomography/computed tomography (PET/CT) imaging with [ 18 F]-fluorodeoxyglucose (FDG) can monitor monkeypox disease progression in vivo in nonhuman primates (NHPs). In this study, we investigated [ 18 F]-FDG-PET/CT imaging of immune processes in lymphoid tissues to identify patterns of inflammation in the monkepox NHP model and to determine the value of [ 18 F]-FDG-PET/CT as a biomarker for disease and treatment outcomes. Quantitative analysis of [ 18 F]-FDG-PET/CT images revealed differences between moribund and surviving animals at two sites vital to the immune response to viral infections, bone marrow and lymph nodes (LNs). Moribund NHPs demonstrated increased [ 18 F]-FDG uptake in bone marrow 4 days postinfection compared to surviving NHPs. In surviving, treated NHPs, increase in LN volume correlated with [ 18 F]-FDG uptake and peaked 10 days postinfection, while minimal lymphadenopathy and higher glycolytic activity were observed in moribund NHPs early in infection. Imaging data were supported by standard virology, pathology, and immunology findings. Even with the limited number of subjects, imaging was able to differentiate the difference between disease outcomes, warranting additional studies to demonstrate whether [ 18 F]-FDG-PET/CT can identify other, subtler effects. Visualizing altered metabolic activity at sites involved in the immune response by [ 18 F]-FDG-PET/CT imaging is a powerful tool for identifying key disease-specific time points and locations that are most relevant for pathogenesis and treatment. IMPORTANCE Positron emission tomography and computed tomography (PET/CT) imaging is a universal tool in oncology and neuroscience. The application of this technology to infectious diseases is far less developed. We used PET/CT imaging with [ 18 F]-labeled fluorodeoxyglucose ([ 18 F]-FDG) in monkeys after monkeypox virus exposure to monitor the immune response in lymphoid tissues. In lymph nodes of surviving monkeys, changes in [ 18 F]-FDG uptake positively correlated with enlargement of the lymph nodes and peaked on day 10 postinfection. In contrast, the bone marrow and lymph nodes of nonsurvivors showed increased [ 18 F]-FDG uptake by day 4 postinfection with minimal lymph node enlargement, indicating that elevated cell metabolic activity early after infection is predictive of disease outcome. [ 18 F]-FDG-PET/CT imaging can provide real-time snapshots of metabolic activity changes in response to viral infections and identify key time points and locations most relevant for monitoring the development of pathogenesis and for potential treatment to be effective.